Information Management - Kaur, Barjinder (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Information management (IM) is the collection and management of information from one or more sources and the distribution of that information to one or more audiences. Management means the organization of and control over the planning, structure and organization, controlling, processing, evaluating and reporting of information activities in order to meet client objectives and to enable corporate functions in the delivery of information. ’Information’ here refers to all types of information of value, whether having their origin inside or outside the organization, including data resources, such as production data; records and files related, for example, to the personnel function; market research data; and competitive intelligence from a wide range of sources. Information management deals with the value, quality, ownership, use and security of information in the context of organizational performance.